An analytical approach to difining strategic options in a case of developing multimodal transport in the Army of Serbia - Ljubojević, Srđan D.; Dimić, Srđan H.; Luković, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Introduction Limited resources in the defense domain impose the acceptance of an analytical, essentially economic, management point of view. There is a necessity to use available resources rationally and to implement sustainable development strategies, defined on the basis of proper understanding and analyses of internal and external environment. Analytical framework for creating a strategy Adequate strategic choices, particularly in military organizations, always ask for analytical arguments. In that sense, an analytical framework for mapping the influencing factors and designing appropriate strategies is proposed. It includes several basic components, although, in principle, its character is situational: experts and expert teams, knowledge management, data collection and processing, prediction and quantification and visualization of expected results. All stakeholders and all who are interested to achieve the ultimate goal should have an active role in this process. Portfolio analysis of movement and transport support One of the most important functions of the Army of Serbia, in the field of logistics support, which requires rapid changes and which is soon necessary to define an adequate strategy of development, is a traffic (movement) and transport function. Taking into account the proposed analytical framework, the roles of specific areas of functioning - aspects of Army transport support are first re-examined through a modified portfolio model McKinsey / General Electric (Matrix of industry attractiveness / business strength). Based on the outcomes of the portfolio analysis of selected aspects, the development of multimodal transport is emphasized as a particularly interesting problem. Analysis of multimodal transport in the Serbian Army The problem of defining the strategy for the development of multimodal transport in the Army is multidisciplinary. It has implications for a wide range of activities. This paper identifies and analyzes the key factors (transportation assets, equipment, infrastructure and organizational structure). It was found that the transportation assets are not compatible with present equipment and mechanization since there is a large variety of basic models of different age structure and dynamics. The equipping with t mechanization, pallets and packing means, in relation to the other structures in the country, is assessed to be good, although not equally distributed. Infrastructure elements, primarily storage and associated facilities (roads, platforms, ramps, etc.), in most cases do not correspond to actual needs. A part of the problem is caused by the organizational structure and defined responsibilities, personnel policy and the policy of personnel education and training. Defining the optimal strategy for multimodal transport development in the Serbian Army For a definition of strategic options, a fuzzy SWOT analysis is used. By interviewing a group of experts, a set of internal and external factors is established and the value of their influence is estimated. The evaluation of the strategic factors is performed by taking the recommended cross-section of alpha (α = 0.5), while the formulation of the strategic options is observed according to the percentage of belonging of the alpha-sectional projection area to a particular "strategic" quadrant. Based on the interconnectedness of the factors, three variants of strategic options for multimodal transport development are extracted. They are measured using the Analytic Hierarchy Process (AHP), and its fuzzy interpretation. This made ​​it possible to adequately treat the uncertainties present in the process of the evaluation of criteria and alternatives. Conclusion During intensive organizational changes in the Serbian Army, technical - technological modernization is especially emphasized. The aim is to use material and human resources more productively and efficiently. In this sense, the definition of the development strategies for all segments of the Army must be the result of an analytically conceived procedure. The procedure itself has a situational character, but there is posibility to identify its basic components and to determine its general contours. The application of the proposed analytical framework foro defining a sustainable strategy is shown using the example of defining the development strategy of multimodal transport in the Serbian Army, through the analysis of the curent situation (Portfolio analysis), definition of strategic development options (fuzzy SWOT analysis) and selection of the best option (fuzzy AHP). In accordance with the general environment conditions and the need for rational use of available resources, a correct and analytically reasoned approach to organizational problems is crucial for the further system development.